360. DIAGNOSIS OF RECURRENT LARYNGEAL NERVE PARALYSIS BY EVALUATING MOVEMENT OF THE VOCAL CORDS USING ULTRASONOGRAPHY AFTER MINIMALLY INVASIVE ESOPHAGECTOMY. (24th September 2022) - Leng, Xuefeng; Teng, Xiangnan; Xu, Shanling; Peng, Lin; Xiao, WenGuang; Fang, Qiang; Han, Yongtao; Zhu, Yi
Abstract: Development of thoracoscopic surgical skills and concepts in minimally invasive esophagectomy (MIE) and robotic-assisted (MIE) have provided us with a more wider anatomical understanding of lymphadenectomy and the relationship between lymph node dissection and recurrent laryngeal nerve paralysis (RLNP). However, RLNP correlates to postoperative complications even in prognosis. Early warning and novel diagnosis are urgent in the management of esophageal cancer patients. Taking a novel approach to researching the diagnosis of RLNP, we evaluated movement of the vocal cords and arytenoid cartilages using ultrasonography in patients who underwent thoracoscopic esophagectomy after extubating of trachea cannula at department of critical care medicine. Further ultrasonography combined endoscopy evaluation and verification were performed on day 5–7 before hospital discharge. RLNP occurred in 4 of the 20 patients' cohort (20%). All of 20 patients were finished ultrasonography combined endoscopy evaluation. The diagnostic accuracy of RLNP by ultrasonography compared to endoscopy had a sensitivity of 100.0% (4/4), a specificity of 87.5% (14/16). The positive predictive value was 66.7% (4/6), negative predictive value was 100.0% (14/14), a false positive rate of 33.3% (2/6), and a false negative rate of 0% (0/14). Ultrasonography is a quite non-invasive and effective measure to diagnose and evaluate RLNP after esophagectomy compared to traditional examination of endoscopy. It also has a perspective future in evaluation for the recovery status of RLNP.